Modeling System Reliability For Digital Preservation: Model Modification and Four-Copy Model Study - Han, Yan (British Library, 2008)
Research has been studied to evaluate the reliability of storage media and the reliability of a computer backup system. In this paper, we use the Continuous Time Markov Chain to model and analyze the reliability of a computer backup system. We propose a modified model from that of the Constantopoulos, Doerr and Petraki [1]. We analyze the difference, show computational results, and propose new input parameters (e.g. time to repair) for the model from our experience. Further we developed a four-copy data model to test if it fulfills the sample reliability rate set by the RLG-NARA. The modeling process can be applied to construct models for computer preservation systems using different storage media. The reliability of constructed models can be calculated so that preservation institutions can have quantitative data to decide their preservation strategies.